2004
DOI: 10.1074/jbc.m406685200
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Tolerance and Coupling of Mitochondrial Electron Transport

Abstract: Oxygen is critical to aerobic metabolism, but excessive oxygen (hyperoxia) causes cell injury and death. An oxygen-tolerant strain of HeLa cells, which proliferates even under 80% O 2 , termed "HeLa-80," was derived from wild-type HeLa cells ("HeLa-20") by selection for resistance to stepwise increases of oxygen partial pressure. Surprisingly, antioxidant defenses and susceptibility to oxidant-mediated killing do not differ between these two strains of HeLa cells. However, under both 20 and 80% O 2 , intracell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 53 publications
3
48
0
Order By: Relevance
“…TMZ-resistant glioma cells through an adaptive remodeling of the ETC activities may have built a more efficient coupling and may have a greater ability to increase mitochondrial electron transport during conditions of bioenergetic demand. This property may confer a selective advantage during the progression of the tumor, in particular under nutrient and hypoxic conditions (21,43,(57)(58)(59)(60). Our data also indicate that FCCP-linked respiration relative to the basal levels (reserve capacity) is higher in TMZresistant glioma cells compared with TMZ-sensitive ones.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…TMZ-resistant glioma cells through an adaptive remodeling of the ETC activities may have built a more efficient coupling and may have a greater ability to increase mitochondrial electron transport during conditions of bioenergetic demand. This property may confer a selective advantage during the progression of the tumor, in particular under nutrient and hypoxic conditions (21,43,(57)(58)(59)(60). Our data also indicate that FCCP-linked respiration relative to the basal levels (reserve capacity) is higher in TMZresistant glioma cells compared with TMZ-sensitive ones.…”
Section: Discussionsupporting
confidence: 69%
“…To examine whether enhanced CcO activity is linked to TMZ resistance to cell killing, we treated UTMZ cells with N-methyl mesoporphyrin IX (NMP), an inhibitor of ferrochelatase that decreases the activity of CcO by preferentially inhibiting heme a synthesis (42,43). Heme a is an essential component of CcO assembly and function with inhibition-blocking CcO activity.…”
Section: Pharmacological Inhibition Of Complexes Ii-iii and IV Activimentioning
confidence: 99%
“…Similarly, addition of the protonophore carbonyl cyanide m-chlorophenylhydrazone (CCCP) to csg2Δ cells suppresses death (Figure 1d), likely by abolishing ROS generation. 19 Both ROS and death in csg2Δ cells are abrogated by overexpression of mitochondrial catalase, encoded by CTA1, which detoxifies hydrogen peroxide generated from superoxide 20 ( Figures 1d and 2a). These results support the hypothesis that ETC-generated ROS promotes cell death.…”
Section: Resultsmentioning
confidence: 99%
“…22,23 Increased ETC activity and O 2 consumption during stress, including nitrogen deprivation, has been suggested to restrict ROS production by increased efficiency of electron transfer. 19,36 ROS production in csg2Δ cells is increased during nitrogen deprivation because the cells are unable to make a metabolic shift to increase respiration, and prevent electron leakage from the respiratory chain to limit ROS production. Nitrogen deprivation signals may also act as a metabolic checkpoint to suppress ATP-consuming activities needed for cell growth and proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study demonstrated that increased complex IV activity leads to lower mitochondrial free radical generation (Campian et al, 2004). Previous work also demonstrated that, on activation, PKC translocates to mitochondria and interacts with components of MPTP resulting in inhibition of its opening (Baines et al, 2003).…”
Section: Pkc Activation Leads To Increased Mitochondrial Etc Efficiencymentioning
confidence: 99%